1998
DOI: 10.1063/1.1148973
|View full text |Cite
|
Sign up to set email alerts
|

Absolute values of specific heat capacity and thermal conductivity of liquids from different modes of operation of a simple photopyroelectric setup

Abstract: Photothermal techniques offer a nice tool for the determination of changes in thermal parameters of different types of samples. Using a very thin pyroelectric transducer, a very simple and versatile ac calorimeter can be built. The described inverse pyroelectric technique allows high-resolution ac-calorimetric measurements of the temperature dependence of the specific heat capacity. Since measuring frequencies up to a few hertz can be used, which are higher than in most alternative ac-calorimetric setups, nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…The theoretical obtained results for higher frequencies [Marín et al, 2010] showed in part (b) of the same figure that the frequency intervals with amplitude ratios greater than unity are awaited to appear in a periodical manner, a typical result for wave phenomena. A similar result has been reported by Depriester et al [Depriester et al, 2005] in the context of the photothermal infrared radiometry technique, and by Caerels et al [Caerels et al, 1998], Longuemart et al and Sahraoui et al ) using a photopyroelectric (PPE) technique. The measurement configuration is very similar as that described above for the PA method.…”
Section: Using This Schema Lima Et Alsupporting
confidence: 71%
See 1 more Smart Citation
“…The theoretical obtained results for higher frequencies [Marín et al, 2010] showed in part (b) of the same figure that the frequency intervals with amplitude ratios greater than unity are awaited to appear in a periodical manner, a typical result for wave phenomena. A similar result has been reported by Depriester et al [Depriester et al, 2005] in the context of the photothermal infrared radiometry technique, and by Caerels et al [Caerels et al, 1998], Longuemart et al and Sahraoui et al ) using a photopyroelectric (PPE) technique. The measurement configuration is very similar as that described above for the PA method.…”
Section: Using This Schema Lima Et Alsupporting
confidence: 71%
“…Suppose that a solid sample is subjected to periodical modulated heating at certain frequencies. Using different detection schemas some authors [Caerels et al, 1998[Caerels et al, ) 2452[Caerels et al, -2458Sahraoui et al, 2002;Depruester et al, 2005;Lima et al, 2006;Marin et al, 2010] have observed that when a sample is in contact with a liquid the resulting sample's temperature may be larger than that due to the bare sample, for certain values of the modulation frequencies. This contradicts the expected behavior that in the presence of a liquid the developed heat will always flow through the sample to the liquid, which acts as a heat sink.…”
Section: A Sample Periodically and Uniformly Heated At One Of Its Surmentioning
confidence: 99%
“…We hope that the here presented model could also be useful for the straightforward interpretation of analogous results in other photothermal experiments, such as those involving thin films on substrates and those based in photopyroelectric (PPE) detection. In some of these, similar effects have been observed using the so-called inverse detection configuration, although the authors of these reports [22,23] do not discuss in detail the cause of the observed increase of the normalized signal above unity. On the other hand, the approach presented here could be helpful not only in the field of photothermal techniques but also open a frame for the analysis of the phenomenon of heat transfer in the presence of modulated heat sources in multilayer structures, which appear frequently in nature and man made devices (for example semiconductor heterostructures lasers and LEDs driven by pulsed, periodical electrical current sources).…”
Section: Discussionmentioning
confidence: 75%
“…(4). D = 7.99 × 10 −4 cm 2 · s −1[6,7].Figures 3-5show the transient signal for refined and thermally treated avocado oils at room temperature. From the best fit of Eq.…”
mentioning
confidence: 99%